Children’s use of teleological explanations about the natural world - Halls, Jonathan Grant (2018)
There is a significant body of research on children's preconceptions concerning scientific concepts and the impact this can have upon their science education. One active issue concerns the extent to which young children's explanations for the existence of natural kinds rely on teleological explanations. These explanations either propose a purpose (e.g., muddy puddles are for jumping in) or suggest goal-driven behaviour (e.g., tigers decided to grow stripes for better camouflage). It has been argued that this teleological tendency is a major barrier to children’s understanding of causality in the natural world, particularly when learning about evolution. This thesis details four studies which explore and seek to limit children’s use of teleological explanations for natural kinds. Study 1 investigated two factors (question wording and questioned topic) that may have led to an overestimation of children's use of teleological explanations for natural phenomena (i.e., time-constrained, natural events or processes such as snow, clouds or night). The findings indicated that children's (aged 5- to 8-years-old, n = 66) responses to open questions involved significantly fewer teleological answers than to the typical leading form used in prior research. Furthermore, the concept of teleology is more nuanced than often suggested, as levels of teleological explanation varied considerably within the category of natural phenomena. Consequently, young children may be more able to learn about causal explanations than the literature implies. Study 1b used methods from corpus linguistics to explore the naturally occurring discourse surrounding the examples of natural phenomena investigated in Study 1. Teleological and scientific patterns of discussion were identified in a specially created corpus of children’s discourse. The results of this analysis indicate that the patterns of language that children experience can influence their use and the form of teleological explanations. Studies 2 and 3 consisted of efficacy tests of an intervention designed to limit children’s endorsement of teleological explanations to account for the existence of a) natural phenomena (e.g., snow or rainbows) and b) organisms’ traits (e.g., giraffes’ necks or zebras’ stripes). The interventions consisted of short discussion-based activities which sought to develop children’s understanding of why teleological explanations are inappropriate to use in scientific contexts. (Study 2, 5- to 7-year-olds, n = 54; Study 3, 9- to 10-year-olds, n = 24). These studies suggest teleology need not be a major barrier to teaching and learning about causality in Early Years education. After only limited discussion about styles of explanation in science, the results revealed that children’s teleological preconceptions were malleable to change, a finding which runs counter to current thinking on children and teleology. In terms of a contribution to knowledge, it is proposed that children’s use of teleological explanations is more nuanced than currently suggested by the literature. Furthermore, children’s use of these explanations can be limited with a series of simple, short discursive lessons. Lessons that do not require additional pedagogical knowledge on the part of primary school teachers.